Model Disiplin Kerja, Iklim Organisasi dan Produktivitas Kerja Pegawai - Ikhsan, Zulfikar; Suwatno, Suwatno; Santoso, Budi (Universitas Pendidikan Indonesia, 2018)
AbstractDemands for productivity are getting higher. The tight competition among retailers causes companies that do not have high productivity to compete. Quality of HR is the key to success. The purpose of the study was to obtain an explanation of the influence of work discipline and organizational climate on the work productivity of employees at PT. Surya Donasin Regional Office Cianjur, which numbered 59 employees randomly selected. The research method uses explanatory survey with multiple linear regression analysis. Based on the results of the research that productivity as one of the keys to compete in the retail industry is determined by work discipline and organizational climate that supports work productivity. Labor productivity is determined by internal and external dynamics in the form of organizational climate. The managerial implication is that the lack of productivity over employees causes low company productivity. Increase productivity as an option to support work productivity.Keywords : Work discipline; organizational climate; productivity; retailer industryÂ AbstrakTuntutan terhadap produktivitas semakin tinggi. Persaingan yang cukup ketat diantara perusahaan retailer menyebabkan perusahaan yang tidak memiliki produktivitas tinggi kalah bersaing. Kualitas SDM menjadi kunci keberhasilan. Tujuan penelitian untuk memperoleh penjelasan tentang pengaruh disiplin kerja dan iklim organisasi terhadap produktivitas kerja para pegawai di PT. Surya Donasin Regional Office Cianjur yang berjumlah 59 pegawai yang dipilih secara acak. Metode penelitian menggunakan survey explanatory dengan analisis regresi linear berganda. Berdasarkan hasil penelitian bahwa produktivitas sebagai salah satu kunci untuk bersaing dalam industri retail ditentukan oleh disiplin kerja dan iklim organisasi yang mendukung produktivitas kerja. Produktivitas tenaga kerja ditentukan oleh dinamika internal dan eksternal berupa iklim organisasi. Implikasi manajerial adalah lemahnya produktivitas pegawai menyebabkan produktivitas perusahaan rendah. Meningkatkan produktivitas sebagai pilihan untuk mendukung produktivitas kerja.Kata Kunci: Disiplin kerja; iklim organisasi; produktivitas; industri retailer